Perspective of a subsidy fraud in Colombian law. An analysis from the public service - Bernal Gómez , Daniel Rigoberto; Díaz Bejarano, Duván Stiven (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Administrative corruption is a recurring phenomenon in many legal systems. In this respect Colombia does not escape these unfortunate maneuvers made by individuals and public servants. This article is a legal review of the phenomenon of subsidy fraud through reflection on it, using the synthetic method, first making an introduction to the constitutional framework of separation of powers of the Colombian State of Law, then in a second section it is taken the doctrinal and comparative law reference, to conclude with some jurisprudential precedents of impact on the Colombian legal system.